PHASE EQUILIBRIA IN THE SYSTEM CACO3-MGCO3-FECO3 - Anovitz L.M.; Essene E.J. (My University, 1987)
Experimental data on phase relations in the CaCO 3 -MgCO 3 -FeCO 3 ternary by Goldsmith et al . (1962) are inconsistent with those of Rosenberg (1967). These inconsistencies cannot be reconciled by the pressure or temperature differences between the two sets of experiments. Available reversed experiments on the binary systems have been re-evaluated to yield consistent binary solvi. These data have been combined with analyses of natural carbonates to yield approximate ternary phase diagrams at 250,400,550, and 700 C, and 4 to model ternary activity/composition relations for calcite- and dolomite-structure carbonates. An empirical model for thermometry with calcite-ferroan dolomite was derived from the ternary solvus by fitting an empirical equation to the calcite limb of the ternary solvus. This model appears to extend reliably to higher iron contents than the models of Bickle * Powell (1977) and Powell et al . (1984).